Hubungan antara Identitas Sosial dan Kesejahteraan Psikologis pada Mahasiswa Baru Psikologi Universitas Negeri Surabaya - Mai Zuhra Nur Azizi; Mimbar Oktaviana (Jurnal Ragam Pengabdian, 2026)
Entering higher education is a critical transition period often accompanied by adaptation challenges that can impact students' mental health. This study aims to analyze the relationship between social identity and psychological well-being among first-year psychology students. Using a quantitative approach with a cross-sectional correlational design, data were collected from 214 first-year students at Universitas Negeri Surabaya through an online questionnaire. The instruments used were the Social Identity Scale and the Psychological Well-being Scale. Data analysis was performed using Spearman rank correlation to determine the strength and direction of the relationship between variables. The results indicated a significant and positive relationship between social identity and psychological well-being. Students with a strong sense of identification with their social group demonstrated higher levels of self-acceptance, positive relations with others, and purpose in life. These findings suggest that social identity serves as a crucial psychological resource that facilitates successful adaptation to the academic environment. It is concluded that fostering social connections and a sense of belonging in the university setting is essential for promoting the psychological well-being of new students.